2021
DOI: 10.52547/jrdms.6.4.23
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges Faced by Senior Dental Students and General Dentists

Abstract: Background and Aim: General familiarity with medical ethics sometimes does not meet the needs of dentists. The aim of this study was to evaluate the ethical challenges faced by senior dental students and dentists. Materials and Methods: In this cross-sectional study, 50 senior dental students and 50 dentists were selected from Yazd city, Iran. A questionnaire with three domains (demographic information, hypothetical scenarios, and some three-choice questions about ethical issues) was used to collect data, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…The fee-related dilemmas of our students were also reported elsewhere with more severe acknowledgment. In the study of Maybodi et al [28], the authors reported that the most common challenges faced by dental students were compromising treatment due to cost issues (77.1%), a percentage almost triple the one reported here. This can be attributed to the chronological challenges of the current worldwide pandemic, cultural differences, and Gen Z characteristics [31,32,36].…”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…The fee-related dilemmas of our students were also reported elsewhere with more severe acknowledgment. In the study of Maybodi et al [28], the authors reported that the most common challenges faced by dental students were compromising treatment due to cost issues (77.1%), a percentage almost triple the one reported here. This can be attributed to the chronological challenges of the current worldwide pandemic, cultural differences, and Gen Z characteristics [31,32,36].…”
Section: Discussionmentioning
confidence: 38%
“…In comparison, only 18% of the postgraduate students claimed the same, and 82% of the dentists, while only 16% of the participants believed this decision would be wrong, stubborn, or show indifference [39]. In accordance, 66% of the students and 89.8% of the dentists in the study of Maybodi et al [28] expressed the right of the clinician to refuse treatment.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In their studies, Raskiliene et al reported a direct relationship between oral hygiene and education level (24)(25)(26)(27). However, in the study by Rashidi-Maybodi et al, no significant relationship was shown between oral health and education level (28).…”
Section: Discussionmentioning
confidence: 93%